Septuagintas betydning som en hellenistisk udgave af Det Gamle Testamente - Müller, Mogens (Dansk Teologisk Tidsskrift, 2011)
The understanding of the role of the old Greek translation of the Old Testament, the Septuagint, has undergone great changes in the last decennia. From looking upon the Hebrew text as the original and the Greek text as only a translation, it has now been common to view the Greek version as a chapter in a reception history of biblical traditions. By being used by New Testament authors and in the Early Church the Septuagint gained canonical status – alongside the Hebrew Bible. Thus the Old Testament of the Church in reality consists of both versions. The article argues for this also pointing to some of the theological consequences of viewing the connection between the two parts of the Christian Bible from the perspective of reception history.